2022
DOI: 10.1155/2022/4623561
|View full text |Cite|
|
Sign up to set email alerts
|

The Design of Sports Games under the Internet of Things Fitness by Deep Reinforcement Learning

Abstract: This study explores the application of deep reinforcement learning (DRL) in the Internet of Things (IoT) sports game design. The fundamentals of DRL are deeply understood by investigating the current state of IoT fitness applications and the most popular sports game design architectures. The research object is the ball return decision problem of the popular game of table tennis robot return. Deep deterministic policy gradients are proposed by applying DRL to the ball return decision of a table tennis robot. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…Consider a team sport like soccer. Reinforcement learning algorithms can analyze vast amounts of historical game data to identify successful strategies for offense, defense, and transitions between the two [11]. By simulating various game scenarios and adjusting tactics based on observed outcomes, these algorithms can suggest optimal formations, player positioning, passing patterns, and defensive structures that maximize the team's chances of scoring goals while minimizing the risk of conceding [12].…”
Section: Introductionmentioning
confidence: 99%
“…Consider a team sport like soccer. Reinforcement learning algorithms can analyze vast amounts of historical game data to identify successful strategies for offense, defense, and transitions between the two [11]. By simulating various game scenarios and adjusting tactics based on observed outcomes, these algorithms can suggest optimal formations, player positioning, passing patterns, and defensive structures that maximize the team's chances of scoring goals while minimizing the risk of conceding [12].…”
Section: Introductionmentioning
confidence: 99%
“…In any strategic scenario, tactical decisions and round planning are pivotal components that can determine the outcome of the entire operation [1]. When faced with complex situations, commanders must meticulously assess their resources, analyze the enemy's strengths and weaknesses, and formulate a cohesive plan that maximizes their chances of success while minimizing risks [2].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%